2014
DOI: 10.1177/2054270414531127
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the acute cardiovascular effects of shisha smoking: a cross-sectional study

Abstract: ObjectivesTo investigate the acute cardiovascular effects of smoking shisha.DesignA cross-sectional study was carried out in six shisha cafes. Participants smoked shisha for a period between 45 min (minimum) and 90 min (maximum). The same brand of tobacco and coal was used.SettingLondon, UK.ParticipantsParticipants were those who had ordered a shisha to smoke and consented to have their blood pressure, heart rate and carbon monoxide levels measured. Excluded subjects were those who had smoked shisha in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 18 publications
1
27
0
Order By: Relevance
“…3 These results were also observed in studies from Jordan and the United Arab Emirates. 16 The parameters described above were notably higher in shisha smokers, compared with cigarette smokers.…”
Section: The Health Effects Of Smoking Shishasupporting
confidence: 74%
See 3 more Smart Citations
“…3 These results were also observed in studies from Jordan and the United Arab Emirates. 16 The parameters described above were notably higher in shisha smokers, compared with cigarette smokers.…”
Section: The Health Effects Of Smoking Shishasupporting
confidence: 74%
“…16 The parameters described above were notably higher in shisha smokers, compared with cigarette smokers. 3 Ultimately, in chronic shisha smokers, systolic blood pressure and heart rate remain signifi cantly elevated. 17 People who smoked both shisha and cigarettes were reported to have the highest mean systolic blood pressure and heart rate, across all age groups.…”
Section: The Health Effects Of Smoking Shishamentioning
confidence: 99%
See 2 more Smart Citations
“…These studies demonstrated that waterpipe acutely increases heart rate and blood pressure in consumers [7]. Chronically WPS is shown to be associated with coronary artery disease [8,9]. The ankle brachial index (ABI) is the ratio of the systolic blood pressure (SBP) measured at the ankle to the brachial artery.…”
Section: Introductionmentioning
confidence: 99%